Establishing a niche in respiratory therapy research: Comparing novice and expert writing - Ashleigh Cox; Eric Friginal (Ibérica)
This study examines the phrases used to highlight research gaps in writing in the respiratory therapy discipline. A corpus of respiratory therapy research article introductions was compiled, and words and phrases associated with signaling research gaps were searched. To compare expert and student writing, the same phrases were searched in a corpus of introductions written by respiratory therapy master’s students. The words however, but, limited, and need were common, but many of the phrases that previous studies have associated with highlighting gaps were not frequently used for this function in either corpus. Master’s students overused the phrases no studies, need, and must. While these findings have pedagogical implications for the phrases that respiratory therapy students can learn for highlighting research gaps, the low frequency of phrases that have traditionally been associated with this function suggests that corpus-driven studies are needed to determine whether writers have shifted towards using other phrases.